2016
DOI: 10.1186/s12885-016-2355-5
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone receptor blockade in human breast cancer cells decreases cell cycle progression through G2/M by repressing G2/M genes

Abstract: BackgroundThe synthesis of specific, potent progesterone antagonists adds potential agents to the breast cancer prevention and treatment armamentarium. The identification of individuals who will benefit from these agents will be a critical factor for their clinical success.MethodsWe utilized telapristone acetate (TPA; CDB-4124) to understand the effects of progesterone receptor (PR) blockade on proliferation, apoptosis, promoter binding, cell cycle progression, and gene expression. We then identified a set of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 46 publications
0
7
0
1
Order By: Relevance
“…Cell culture T47D cells were grown for 48 h with RPMI containing charcoaltreated FBS as described previously (Reyes et al 2014;Clare et al 2016). Cells were then switched to a medium without serum (288 mOsm) for 18 h prior to treatment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell culture T47D cells were grown for 48 h with RPMI containing charcoaltreated FBS as described previously (Reyes et al 2014;Clare et al 2016). Cells were then switched to a medium without serum (288 mOsm) for 18 h prior to treatment.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, an increase of osmolarity has a rapid strong effect on chromatin organization. To assess chromosome organization, we harvested T47D cells that were maintained in isotonic medium or were exposed to mild hyperosmotic stress (110 mM NaCl) for 1 h, and performed in situ Hi-C. We used arrested T47D cells to eliminate possible effects of stress on cell cycle progression that could lead to indirect differences in chromosome organization (Reyes et al 2014;Clare et al 2016;Nagano et al 2017). Of note, exposure to mild hyperosmolarity did not affect cell viability even at higher NaCl doses (up to 200 mM) and a longer exposure (Supplemental Fig.…”
Section: Hyperosmotic Stress Perturbs A/b Compartment Organizationmentioning
confidence: 99%
“…Activated PR is a context-dependent mitogen in these cancers and it is known that PR independently governs estrogen action and breast cancer biology (3)(4)(5). We and others have previously reported that selective progesterone receptor modulators (SPRMs) inhibit proliferation of PR-positive breast cancer cell lines and suppress rodent mammary tumor formation in a progestin-rich environment (6)(7)(8)(9)(10). In addition, mifepristone (RU486) reduces proliferation in normal breast tissue (11), and progestin exposure contributes to higher breast cancer risk in postmenopausal women (12).…”
Section: Introductionmentioning
confidence: 99%
“…Telapristone is a selective progesterone modulator (SPRM), and we have implemented a chemoprevention trial of LTT to the breast (ClinicalTrials.gov: NCT02314156). As a SPRM, telapristone leads to progesterone receptor blockade leading to changes in gene expression and deceasing progression of a mutated cell through the cell-cycle progression (69). In preclinical testing, topical telapristone has been studied in comparison with systemic telapristone delivered subcutaneously in a multi-arm trial involving athymic nude rats with primary focus on tissue and plasma concentrations (70).…”
Section: Approach To Prevention: Local Transdermal Therapymentioning
confidence: 99%